Are All Substance-Involved Sexual Assaults Alike? A Comparison of Victim Alcohol Use, Drug Use, and Combined Substance Use in Sexual Assaults - O’Callaghan, Erin (Women & criminal justice, 2024)
Sexual assaults involving victim substance use at the time of the assault are common, but little is known about how different types of substances used at the time of the assault impact post-assault outcomes. The current study sought to compare victim alcohol use, drug use, and combined substance use in sexual assaults among a community sample of 693 victims. It was hypothesized that victims in the combined substance use assault type would report overall worse post-assault outcomes, more contextual and interpersonal traumas, and higher assault severity. Our results partially confirmed these hypotheses, but victims in the drug-involved assault type group overall reported higher assault severity and worse post-assault outcomes. These findings are probably partially attributed to the demographic characteristics of victims in the drug-only group (e.g., Black victims) who are more likely to experience a higher severity of violence. Implications for future research and policy regarding drug decriminalization are discussed.